Comparative evaluation of tensile strength, tear strength, color stability and hardness of conventional and 1% trisnorbornenylisobutyl polyhedralsilsesquioxane modified room temperature vulcanizing maxillofacial silicone after a six month artificial aging period - Drashti Sunil Gandhi; Rajesh Sethuraman (Wolters Kluwer Medknow Publications, 2022)
Aims: Silicone elastomers, chemically known as polydimethylsiloxane used in maxillofacial rehabilitation, over a period of time, undergo degradation and discoloration once aged, thereby reducing clinical longevity. Many previous studies reinforced the maxillofacial silicone material with stronger materials to increase its mechanical properties. However, no studies have been conducted to evaluate all the primary properties using single reinforcing agent. This study was conducted to evaluate and compare the tensile strength, tear strength, color stability, and Shore A hardness of conventional and 1% trisnorbornenylisobutyl polyhedralsilsesquioxanes (POSS) modified room temperature vulcanizing (RTV) maxillofacial silicone after a 6 - month artificial aging period. Setting and Design: In vitro comparative study. Materials and Methods: Eighty-eight silicone samples were fabricated. Therefore for each parameter of tensile strength, tear strength, color stability and hardness, twenty two samples comprising of 11 samples of conventional RTV silicone (Group 1) and 11 for POSS modified RTV silicone (Group 2) were fabricated in stainless steel molds using ASTM D 412-06, ASTM D 624, and ASTM D 2240-15 Standards. Baseline measurements for Shore A hardness and color values were recorded. Samples were then exposed to 6 months of natural weathering process and evaluated for tensile and tear strengths, color stability (ΔE), and hardness. Statistical Analysis Used: Paired and unpaired t-test. Results: Intragroup and intergroup comparison was done using unpaired and paired t-test. At the end of 6-month aging period, the tensile strength and tear strength of POSS-modified RTV silicone were significantly higher than conventional RTV silicone (P < 0.0001 and P = 0.00014, respectively). Intragroup comparison of conventional group showed highly statistically notable changes in L, a, and b values (P = 0.01631, > 0.0001, and = 0.0.0067, respectively), whereas the POSS-modified RTV silicone showed statistically nonsignificant results in L, a, and b values' (P = 0.91722, 0.15174, and 0.10847, respectively) comparisons after aging. Intergroup ΔE value comparisons showed an extremely statistically difference (P < 0.0001) within the groups. Intergroup comparisons postaging hardness showed a high statistical difference between both the groups, indicating a significant increase in hardness in the conventional group (P < 0.0001). However, intragroup comparison for hardness values showed a statistically highly significant difference for Group 1 (P < 0.0001) and a nonsignificant difference (P = 0.4831) for Group 2. Conclusion: After the simulated 6-month aging procedure, 1% NB 1070 trisnorbornenylisobutyl POSS-incorporated RTV maxillofacial silicone showed better tensile strength, tear strength, Shore A hardness and color stability as compared to conventional RTV silicone. Hence, trisnorbornenylisobutyl POSS is a potent cross-linking agent which enhances the primary mechanical properties of RTV silicone can result in in significant increase in the mean life expectancy of RTV silicone even after 6 months of weathering.